Combinatorial Chemistry: A Guide for Librarians. - Philip Barnett (Issues in Science and Technology Librarianship)
In the 1980s a need to synthesize many chemical compounds rapidly and inexpensively spawned a new branch of chemistry known as combinatorial chemistry. While the techniques of this rapidly growing field are used primarily to find new candidate drugs, combinatorial chemistry is also finding other applications in various fields such as semiconductors, catalysts, and polymers. This guide for librarians explains the basics of combinatorial chemistry and elucidates the key information sources needed by combinatorial chemists.